The consequences of non-E.U. labor instability - Oprescu Georgiana, (Technium Social Sciences Journal, 2020)
This study focuses on a current problem arising from the lack of labor force on the Romanian market and the solution to this problem that lies in the employment of NON-EU citizens. During the study of this issue, we analyzed aspects related to the irregularities caused by foreigners who have the right to work in Romania, a right that they obtain by the Romanian employer’s fulfilling of the conditions stipulated by art. 36 of the Labor Code, respectively by obtaining the work permit and the residence permit. Another alarming problem is the lack of a clear, concise and strict procedure, which is in line with fundamental human rights. The material and image harm exclusively caused by the lack of labor force is also created by the lack of loyalty of the NON-EU citizen and by the fact that he/she considers Romania only a launching pad to Europe. In the case of seasonal activities, it is imperative that the employer be able to rely on labor security, otherwise there may occur both image and material harm, caused by an uncollected profit. These damages can be difficult to repair or recover, sometimes there is a risk that they can never be repaired or recovered. Based on the strong demand for workforce, entrepreneurs take the risk of engaging in everything that means complying with and fulfilling the prior procedures represented by obtaining a work permit, hiring foreigners and obtaining residence permits for them. However, there is also a risk that, following the completion of all prior formalities and procedures in order to obtain residence permits, NON-EU citizens end up having the right and even decide to do so to terminate employment, choosing to enter into contractual relationships with other companies. Even if the initial employing company, which made every effort to provide a residence - a mandatory condition for obtaining a residence permit, accommodation and meals for the NON-EU citizen and training, could recover part of the damage. caused if the citizen is legally employed in another company, by instituting the seizure of one third of the salary following the trial of the case and the issuance of an enforceable title, this being a difficult and lengthy procedure, damages to the image are also created due to the fact that the company had an organization and an organization chart that was turned upside down by the lack of foreign employee.